Comorbidities and Ethnocultural Factors Limit the Physical Activity of Rural Sri Lankan Patients with Diabetes Mellitus - Arjuna Medagama; Manoj Galgomuwa (Journal of Diabetes Research)
South Asians have high prevalence of diabetes, cardiovascular risk, and physical inactivity. Reasons for physical inactivity have not been explored among Asians living within their endogenous environments. During phase 1 of the study, we assessed the physical activity (PA) of the population using a quantitative, descriptive, cross-sectional research method. During phase 2 of the study, a qualitative method with in-depth interviews was used to collect data on barriers of PA. Four hundred patients with type 2 diabetes, comprising 113 (28.2%) males and 287 (71.7%) females, were enrolled. The overall prevalence of physical inactivity was 21.5% (males: 15.9%, females: 23.7%). The majority (44.8%) of the study population was active and 33.8% were minimally active. The mean weekly MET minutes was 4381.6 (SD 4962). The qualitative study (n=45) identified health-related issues—lifestyle and time management and social embarrassment, prioritizing household activities over PA as significant factors that limited PA.